Estimating the production function for human capital: Results from a randomized control trial in Colombia - Orazio Attanasio; Sarah Cattan; Emla Fitzsimons; Costas Meghir; Marta Rubio-Codina (Yale University, Economic Growth Center, 2015)
We examine the channels through which a randomized early childhood intervention in Colombia led to significant gains in cognitive and socio-emotional skills among a sample of disadvantaged children. We estimate production functions for cognitive and socio-emotional skills as a function of maternal skills and child's past skills, as well as material and time investments that are treated as endogenous. The effects of the program can be fully explained by increases in parental investments, which have strong effects on outcomes and are complementary to both maternal skills and child's past skills.
Keywords: 330